Impact of rpoB Mutations on Reduced Vancomycin Susceptibility in Staphylococcus aureus - Watanabe, Yukiko (American Society for Microbiology, 2011)
Of 38 vancomycin-intermediate Staphylococcus aureus (VISA) clinical strains, 27 (71%) possessed a mutation(s) in rpoB encoding the β-subunit of RNA polymerase. Furthermore, 95.6% of the rifampin-resistant mutants obtained from 9 methicillin-resistant S. aureus (MRSA) clinical isolates showed decreased vancomycin susceptibilities. These data indicate the involvement of an rpoB mutation in VISA phenotype expression.